The relationship between social presence and cognitive load. Issue 2 (17th June 2019) - Costley, Jamie
Abstract : Purpose: As online learning has become more prevalent, how learners interact with each other in those learning environments has become more salient. To develop effective levels of interaction, students must feel comfortable to express their ideas and views. For this reason, this paper aims to look at how individual students' levels of social presence affect germane cognitive load. Germane cognitive load is the amount that students are able to construct schema and can be seen as analogous to learning. Design/methodology/approach: This study looks at the results of survey data ( n = 433) that investigate the relationship between social presence and germane cognitive load. The students were surveyed from the Open Cyber University of Korea in the fall semester of 2018. Findings: The present study found a statistically significant positive relationship between social presence and germane cognitive load. The study found a Spearman's correlation coefficient of 0.595. Furthermore, the sample was divided into a high, medium and low grouping of social presence. Among these groupings, the high level social presence had the highest level of germane cognitive load, and the low level social presence had the lowest level of germane cognitive load. Originality/value: This result shows the importance and value of developing levels of social presence in online environments. Some research has shown relationships between student interaction and learning, but the present study looks directly at social presence and germane cognitive load. From this research, the authors can see the value of encouraging higher levels of social interaction in online learning environments.